ANXIETY OF FINAL STUDENTS WHO HAVE NOT YET STARTED THEIR THESIS IN FACING THE QUESTION 'WHEN WILL THEY GRADUATE?': SELF-EFFICACY ANALYSIS - Siti Putri Astuti; Nuril Hidayanti S (Jurnal Konseling Pendidikan Islam, 2026)
Final year students often experience academic stress, pressure from family, and increased anxiety when facing the demands of preparing a thesis. This study aims to understand the dynamics of academic anxiety experienced by final year students who have not yet started preparing their thesis, especially when facing social questions about their academic progress. This study uses a qualitative approach with a case study design for one subject from the class of 2020 who experienced difficulties in starting a thesis due to academic pressure, family expectations, and negative experiences from others. Data were collected through in-depth interviews, non-participant observations, and document analysis related to the subject's academic behavior. Data analysis was carried out with a thematic approach based on four sources of self-efficacy, according to Bandura. The results showed that the subjects' low self-efficacy was related to a lack of experience of academic success, negative experiences from family members who did not complete their studies, a lack of motivational verbal support, as well as physiological and emotional conditions characterized by excessive anxiety. Social questions like "when to graduate?" serve as anxiety triggers that reinforce patterns of academic avoidance. This study concludes that obstacles in starting a thesis are not only related to time management, but are also influenced by the interaction between psychological factors, family environment, and socio-cultural context. These findings are expected to be the basis for guidance and counseling services in providing interventions to improve the self-efficacy of final year students.